Genetic diversity and phylogeography of the endemic species Chimonobambusa utilis growing in southwest China: Chloroplast DNA sequence and microsatellite marker analyses - Liu, Yanjiang; Wu, Mingli; Xu, Xue; Zhu, Xiao; Dai, Zhaoxia; Gou, Guangqian (Frontiers in Plant Science, 2022)
Chimonobambusa utilis (Keng) Keng F is an endemic species distributed only in the Daluoshan Mountains, southwest China. Ch. utilis is popular due to its unique flavor and deliciousness and plays an important role in the industrial revolution in many counties in China. A total of 20 natural populations were sampled from the entire distribution range of Ch. utilis. In the present study, we used five EST-SSR molecular markers, three chloroplast DNA (trnH-psbA, atpF-atpH, and psbK-psbI), and one ITS molecular marker to elucidate the genetic diversity and phylogeography analyses of these Ch. utilis populations. The results exhibited that Ch. utilis populations showed lower genetic diversity than other angiosperms (HT = 0.752, HS = 0.364, and FST = 0.05021 for EST-SSR; HT = 0.956, Hs = 0.507, and FST = 0.70121 for cpDNA; HT = 0.868, Hs = 0.495, and FST = 0.70121 for nrDNA). A total of 40 alleles were detected for five polymorphic loci. We detected 20 polymorphic sites and 11 haplotypes within 1,398 bp of cpDNA and 59 polymorphic sites and 32 haplotypes within the 589 bp of the ITS sequence. Based on the haplotype distribution, we infer that there were at least two glacial refuges of Ch. utilis populations during the Quaternary Ice Age. The genetic and geographic distance were correlated (p < 0.05), indicating that narrow distribution might be the primary cause of the low genetic differentiation of Ch. utilis populations. Based on the genetic diversity of Ch. utilis populations, we recommend implementing effective genetic resource management and sustainable utilization.